Pembelajaran Saintifik Berbantuan Geogebra untuk Meningkatkan Penalaran Siswa Kelas VIII SMP pada Materi Lingkaran - Syaeruldinata, Apdwi (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
The aim of this study is to describe the implementation of scientific learning assisted by GeoGebra media that can improve the reasoning of Grade VIII junior high school students on the topic of circles. This research is a classroom action research conducted in two cycles, with each cycle consisting of four components: planning, action, observation, and reflection. The participants in this study were students of class VIII.1A at SMPN 3 Gangga, and it was carried out in the second semester of the 2022/2023 academic year. Data collection used test sheet instruments. The results of the study showed that there was an increase in students' reasoning from 62.5% in cycle 1 to 81.25% in cycle 2. Thus, scientific learning assisted by GeoGebra can improve students' reasoning on the topic of circles with the following stages: (a) the observing stage, which involves paying attention to something using the senses, not limited to the sense of sight but also other senses, such as reading, listening, watching, and so on, (b) the questioning stage, which stimulates students' curiosity, leading to a desire to conduct further investigation related to the observed object through questions, (c) the data collection stage, which is a follow-up to the questioning activity, (d) the associating stage, where the collected data is linked to answer the problem formulation in the questioning stage, and (e) the communicating stage, which involves sharing or presenting a summary of the learning activities from observing to associating through various means, both orally, in writing, presentations, images, reports, tables, graphs, and so on.